Catalytic and non-catalytic synergistic effects and their individual contributions to improved combustion performance of coal/biomass blends. (1st February 2018) - Oladejo, Jumoke; Adegbite, Stephen; Gao, Xiang; Liu, Hao; Wu, Tao
Highlights: Catalytic and non-catalytic synergistic effects on co-firing were distinguished. Extent of synergistic effects were found dependent on coal constituents and rank. Non-catalytic synergistic effect was found more pronounced in fuel blends. Synergistic inhibition might occur as a result of competing synergistic effects. Individual contribution of catalytic and non-catalytic synergy was quantified. Abstract: This study focuses on the synergistic properties of three types of coal when co-fired with oat straw at different blending ratios. The results demonstrated non-additive interaction between oat straw and coal samples. The catalytic effect of oat straw ash and the non-catalytic effect of its organic constituents on these coal samples were isolated and analysed to measure their contribution to the confirmed synergistic effects during co-firing. The results showed a level of synergy suppression between catalytic and non-catalytic effects due to the overlapping function of the catalytic AAEMs and the radical propagation promoted by organic content of biomass. A novel index, i.e., synergy combination efficiency, was therefore proposed and used to quantify the level of synergistic promotion or synergistic inhibition occurring during the co-firing of these fuel blends. It was found that at a blending ratio of 30 wt% oat straw, the Guizhou coal achieved a synergy factor (S.F) of 1.50, with non-catalytic and catalytic synergy contributing 69.1% and 30.9% respectively. This coal blend showed the highest synergistic promotion with a combined efficiency of 194%, which demonstrated the potential of the use of co-firing synergy to improve combustion performance of poor quality coals.